Digital literacy, entrepreneurial knowledge, and internal locus of control as predictors of entrepreneurial interest among Indonesian economics education students - Anggraini, Alifah Dwi; Sakti, Norida Canda; Fitrayati, Dhiah (Journal of Management and Digital Business, 2026)
High unemployment rates among college graduates and low interest in entrepreneurship among students are pressing issues in Indonesia's economic development. This study examines how digital literacy, entrepreneurial knowledge, and internal locus of control influence entrepreneurial interest among economics students at Surabaya State University. Using a quantitative approach and explanatory research design, this study involved 171 participants obtained through random sampling. Data analysis was performed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) through the WarpPLS application. The results of the study demonstrate that entrepreneurial interest is positively and significantly impacted by all three variables. Among the three, entrepreneurial knowledge emerged as the dominant factor, followed by digital literacy and internal locus of control. Overall, this research model was able to explain 48% of the variation in entrepreneurial interest.